Use of parenteral vitamin B complexes in treatment of polyneuropathy - O. V. Kurushina; A. E. Barulin; O. I. Agarkova (Медицинский совет, 2018)
The article considers the ethiological factors for the formation of such a widespread disease of the peripheral nervous system as polyneuropathy. The classification, modern approaches to the diagnosis of various types of diseases are presented. The authors emphasize on the therapeutic approaches to the treatment of such common forms as diabetic and alcoholic polyneuropathies. Particular attention is paid to the complex of B vitamins. The effectiveness and safety of the injectable form of vitamins for the therapy of polyneuropathies are demonstrated.